Household livelihood change under the rocky desertification control project in karst areas, Southwest China. (November 2016) - Zhang, Junyi; Dai, Minghong; Wang, Lachun; Su, Weici
Highlights: RDCP significantly improved the household livelihood diversification. RDCP has no direct or significant impact on household's income. Farmers emphasize short-term and high profits when they choose alternative livelihoods. Farmers' concern on ecology and their dependence on resources are positively related. Abstract: The Rocky Desertification Control Project (RDCP) has become an important government measure to prevent soil erosion, restore vegetation, and pull farmers out of poverty in the karst areas of Southwest China. In order to understand the impact of the RDCP on households' livelihoods, we surveyed 150 households and collected a total of 117 valid questionnaires in 2013 to analyze the impact of the RDCP on their livelihoods and their livelihood response of the project. The results showed that RDCP significantly improved the process of household livelihood diversity and non-agriculturalization, and a distinct non-agricultural transfer of the rural labor force appeared after the RDCP implementation, characterized mainly by off-farm employment. But RDCP has no direct or significant impact on the increase of households' income which is primarily due to off-farm employment income. Although farmers emphasized on earning profits in the short run when they choose alternative livelihoods in the future, their choices are significantly impacted by the individual conditions. Furthermore, 38.5% of the households considered returning to agricultural production. Besides, households' concern on ecological environment is positively related with their dependence on environmental resources. To prevent a return to agriculture, it is important to develop compensation policies, to create new jobs, and to provide job training to help households construct new alternatives to returning to old livelihoods.